Mining bacterial communities from antarctica and the sub-Antarctic Marion Island as a source of novel antibiotics - Kipandula, Wakisa (Rhodes University, 2026)
Embargo applied. Embargo period to expire in October of 2026.
Keywords: Uncatalogued